2016
DOI: 10.1177/0883073816671855
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Features of Idiopathic Intracranial Hypertension in Children

Abstract: Magnetic resonance imaging (MRI) signs of elevated intracranial pressure and idiopathic intracranial hypertension have been well characterized in adults but not in children. The MRIs of 50 children with idiopathic intracranial hypertension and 46 adults with idiopathic intracranial hypertension were reviewed for optic nerve head protrusion, optic nerve head enhancement, posterior scleral flattening, increased perioptic cerebrospinal fluid, optic nerve tortuosity, empty or partially empty sella, tonsillar herni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 20 publications
6
24
0
Order By: Relevance
“…The widening of the perineural space surrounding the optic nerve and the corresponding increased ONSD values are secondary to the increased ICP and correlate with signs of cerebral hypertension detected using other neuroimaging techniques [21,22]. This finding is easily explained by the connection of the perineural space surrounding the optic nerve with the meninges of the central nervous system.…”
Section: Discussionmentioning
confidence: 85%
“…The widening of the perineural space surrounding the optic nerve and the corresponding increased ONSD values are secondary to the increased ICP and correlate with signs of cerebral hypertension detected using other neuroimaging techniques [21,22]. This finding is easily explained by the connection of the perineural space surrounding the optic nerve with the meninges of the central nervous system.…”
Section: Discussionmentioning
confidence: 85%
“…A number of radiographic findings have been associated with pseudotumor cerebri syndrome. 31,32 In our study, we found a relatively low percentage of patients with MRI abnormalities (approximately 20% of patients) (see Table 4). In the pseudotumor cerebri syndrome imaging literature, which is predominantly focused on adult pseudotumor cerebri syndrome, MRI abnormalities have been identified in up to 90% of patients.…”
Section: Discussionmentioning
confidence: 48%
“…Interestingly, findings such as scleral flattering, transverse sinus stenosis and sella turca (Fig. ) changes were reported at lower frequencies in prepuberal children compared to adolescents and adults in a case series by Hartmann et al, probably due to shorter duration of symptoms in this group. Except for meningoceles, all radiological signs of increased intracranial pressure previously described for adults have been identified in children.…”
Section: Secondary Causesmentioning
confidence: 99%